Impact of Psychophysiological Factors on Academic Performance and Adaptation of First-Year University Students - o’g’li , Nuraliyev Akmal Akram; qizi, Xurramova Sevara Ilxom; Boymuratovna , Buranova Gulnoza (American Journal of Biology and Natural Sciences, 2026)
This study examines how psychophysiological factors influence academic performance and adaptation in first-year university students. Visual memory, attention, and visuomotor reaction speed were assessed at three stages of the 2024–2025 academic year: beginning, pre-examination, and post-examination. Results indicated that students’ memory and attention generally improved throughout the year, while visuomotor reaction speed temporarily declined after exams. Female students demonstrated slightly better cognitive performance than males. These findings suggest that psychophysiological indicators play a critical role in facilitating adaptation to the educational process and improving learning efficiency.